why does log a + log b = log (ab)

  • Google+ icon
  • LinkedIn icon

Let log a be some number A and log b be some number B

now the natural log of something is the equivalent of saying a=e^A and b = e^B

So a*b = e^A * e^B which by rules of indices

 = e^(A+B)

Therefore log(ab) = log(e^(A+B))

= A + B = log a + log b 

Rebecca V. A Level Maths tutor, 13 plus  Maths tutor, GCSE Maths tuto...

About the author

is an online A Level Maths tutor with MyTutor studying at Bristol University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss